2019
DOI: 10.29327/24816.4.2-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between P561T polymorphism in growth hormone receptor gene and mandibular prognathism: systematic review and metaanalysis

Abstract: Por meio de uma revisão sistemática e meta-análise, o objetivo deste estudo foi avaliar a associação entre o polimorfismo P561T em GHR (rs6184) com a maloclusão de Classe III esquelética em diferentes populações. Métodos: Uma ampla pesquisa de estudos foi realizada utilizando os bancos de dados PubMed, Web of Science, Scopus, Cochrane, Google Scholar e Open Grey até dezembro de 2018. O desenho do estudo de acordo com o PECOS foi: P-Pacientes ortodônticos; Polimorfismo P561T em GHR; Causência de polimorfismo P5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that MR was associated with SNPs in various genes such as Myosin 1H ( MYO1H ) [ 9 ], Matrilin 1 ( MATN1 ) [ 7 ], ADAM Metallopeptidase with Thrombospondin Type 1 Motif 9 ( ADAMTS9 ) [ 10 ], and Bone Morphogenic Protein 2 ( BMP2 ) [ 11 ] genes. In addition, SNPs in the gene encoding growth hormone receptor (GHR) have been associated with variations in the mandibular pattern including prognathism [ 5 , 12 ], supporting that genes coding for hormones, hormone receptors, hormone precursors, and molecules involved in hormonal synthesis could also be involved in the etiology of other phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that MR was associated with SNPs in various genes such as Myosin 1H ( MYO1H ) [ 9 ], Matrilin 1 ( MATN1 ) [ 7 ], ADAM Metallopeptidase with Thrombospondin Type 1 Motif 9 ( ADAMTS9 ) [ 10 ], and Bone Morphogenic Protein 2 ( BMP2 ) [ 11 ] genes. In addition, SNPs in the gene encoding growth hormone receptor (GHR) have been associated with variations in the mandibular pattern including prognathism [ 5 , 12 ], supporting that genes coding for hormones, hormone receptors, hormone precursors, and molecules involved in hormonal synthesis could also be involved in the etiology of other phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The GG and GA genotypes were identified in the Myosin 1H gene and the CC, CA, and AA genotypes were identified in the P561T gene, this is in accordance the study of Tassopoulou-Fishel et al ., 2012. [ 10 11 20 29 30 31 32 33 34 ]…”
Section: Discussionmentioning
confidence: 99%